InsectBase 2.0: a comprehensive gene resource for insects. Issue Volume 50:Issue D1(2022) (18th November 2021) - Mei, Yang; Jing, Dong; Tang, Shenyang; Chen, Xi; Chen, Hao; Duanmu, Haonan; Cong, Yuyang; Chen, Mengyao; Ye, Xinhai; Zhou, Hang; He, Kang; Li, Fei
Abstract: Insects are the largest group of animals on the planet and have a huge impact on human life by providing resources, transmitting diseases, and damaging agricultural crop production. Recently, a large amount of insect genome and gene data has been generated. A comprehensive database is highly desirable for managing, sharing, and mining these resources. Here, we present an updated database, InsectBase 2.0 (http://v2.insect-genome.com/ ), covering 815 insect genomes, 25 805 transcriptomes and >16 million genes, including 15 045 111 coding sequences, 3 436 022 3′UTRs, 4 345 664 5′UTRs, 112 162 miRNAs and 1 293 430 lncRNAs. In addition, we used an in-house standard pipeline to annotate 1 434 653 genes belonging to 164 gene families; 215 986 potential horizontally transferred genes; and 419 KEGG pathways. Web services such as BLAST, JBrowse2 and Synteny Viewer are provided for searching and visualization. InsectBase 2.0 serves as a valuable platform for entomologists and researchers in the related communities of animal evolution and invertebrate comparative genomics.